Omnichannel marketing in the retailing landscape - Hänninen, Sarah (2024)
Today consumers are expecting more coherent customer experiences across online and offline channels to leverage the positive effects of both channels. Omnichannel marketing has met these expectations as it has been defined as integrated customer experience via communication and distribution channels. Still, even though the positive effects of omnichannel marketing are acknowledged and managers perceive it important, only 3% of retailers have all channels connected. To find an answer to that gap, this master’s thesis examined from a management’s point of view (1) what drivers guide retailers to be omnichannel, and (2) which factors affect the implementation of an omnichannel strategy. The study was carried out as a case study, in which retailers from various trade sectors in Finland participated. In total eight people were interviewed from seven companies, and the interviews were carried out using semi-structured interviews, which included some freedom to modify the questions to each person’s knowledge.